Effect of Islamic corporate governance on customer trust: empirical study on Islamic bank - Agung Budi Sulistiyo; Siti Maria Wardayati; Arif Hidayatullah; Shita Silvia Nahdia Riesky (Asian Journal of Islamic Management (AJIM), 2020)
Purpose: This study aims to analyze the effect of Islamic corporate governance and shariah compliance on customer trust in Islamic bank.Methodology: The research method used is a quantitative method with random sampling technique. The data analysis technique used is descriptive statistics and multiple linear regression techniques to test the hypothesis.Findings: The results of the study show that (1) out of the five principles of GCG (transparency, accountability, responsibility, independency and fairness) only transparency has a positive effect on customer trust as indicated by a significance value of 0.047. (2) shariah compliance has a positive effect on customer trust, besides that shariah compliance is a very large indicator contributing to increase customer trust, indicated by a significance value of 0,000.Originality: As far as we are concerned, only a few publications examined the effect of Islamic corporate governance and shariah compliance on customer trust in Islamic bank.